Self instruction techniques recommends using the trend of student "smartphone addiction" to increase self-esteem - Majdi, M. Zuhdi Zainul; Mafirja, Sulma; Maranata, Phina (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Smartphone addiction is a phenomenon that readily occurs in adolescents and harms physical and mental development. One of the factors that influence the occurrence of smartphone addiction in adolescents is low self-esteem. The purpose of this study was to test the effectiveness of group counseling using self-instruction techniques to increase students' self-esteem and make them vulnerable to smartphone addiction. This study used a pre-test and post-test design from a random control group, involving 7 XII students majoring in fashion at SMK Negeri 1 Takengon. The data analysis technique used is repeated measurement analysis of variance. The results showed that the self-instruction technique group counseling can effectively increase the self-esteem of students who tend to be addicted to smartphones in Takengon City, Aceh